Association of COPD With Risk for Pulmonary Infections Requiring Hospitalization in HIV-Infected Veterans. (1st November 2015) - Attia, Engi F.; McGinnis, Kathleen A.; Feemster, Laura C.; Akgün, Kathleen M.; Butt, Adeel A.; Graber, Christopher J.; Fine, Michael J.; Goetz, Matthew B.; Rodriguez-Barradas, Maria C.; Pisani, Margaret A.; Tindle, Hilary A.; Brown, Sheldon T.; et al.
Abstract : Background: Pulmonary infections remain more common in HIV-infected (HIV+) compared with uninfected individuals. The increase in chronic lung diseases among aging HIV+ individuals may contribute to this persistent risk. We sought to determine whether chronic obstructive pulmonary disease (COPD) is an independent risk factor for different pulmonary infections requiring hospitalization among HIV+ patients. Methods: We analyzed data from 41, 993 HIV+ Veterans in the nationwide Veterans Aging Cohort Study Virtual Cohort from 1996 to 2009. Using International Classification of Diseases, Ninth Revision codes, we identified baseline comorbid conditions, including COPD, and incident community-acquired pneumonia (CAP), pulmonary tuberculosis (TB), and Pneumocystis jirovecii pneumonia (PCP) requiring hospitalization within 2 years after baseline. We used multivariable Poisson regression to determine incidence rate ratios (IRRs) associated with COPD for each type of pulmonary infection, adjusting for comorbidities, CD4 + cell count, HIV viral load, smoking status, substance use, vaccinations, and calendar year at baseline. Results: Unadjusted incidence rates of CAP, TB, and PCP requiring hospitalization were significantly higher among persons with COPD compared to those without COPD (CAP: 53.9 vs. 19.4 per 1000 person-years; TB: 8.7 vs. 2.8; PCP: 15.5 vs. 9.2; P ⩽ 0.001). In multivariable Poisson regression models, COPD was independently associated with increased risk of CAP, TB, and PCP (IRR: 1.94, 95% confidence interval [CI]: 1.64 to 2.30; IRR: 2.60, 95% CI: 1.70 to 3.97; and IRR: 1.48, 95% CI: 1.10 to 2.01, respectively). Conclusions: COPD is an independent risk factor for CAP, TB, and PCP requiring hospitalization among HIV+ individuals. As the HIV+ population ages, the growing burden of COPD may confer substantial risk for pulmonary infections. Abstract : Supplemental Digital Content Is Available in the Text.